Identifikasi Gaya Kepemimpinan Kepala Sekolah PAUD Di Gugus 2 Lingsar - Dila, Nurul Fadillah; Jaelani, Abdul Kadir; Rachmayani, Ika (Mataram University, 2025)
The purpose of this study is to identify the leadership styles of early childhood education (PAUD) principals in Cluster 2 Lingsar. A total of 34 PAUD teachers from Cluster 2 Lingsar participated as research subjects. This study employed a quantitative survey method to obtain an objective and measurable overview of the phenomena. Data were collected through questionnaires and documentation using a Likert scale divided into three categories of leadership styles: authoritarian, democratic, and laissez-faire. Descriptive statistical methods, including mean scores, frequencies, and percentages, were used to analyze the data. The results indicate that the democratic leadership style ranked the highest, with a percentage of 83.5%. Meanwhile, the authoritarian leadership style scored 49.2%, and the laissez-faire style 52.6%, both falling within the moderate category. These findings suggest that PAUD principals in Cluster 2 Lingsar generally apply an active participatory leadership style characterized by collaborative decision-making, open communication, a supportive work atmosphere, guidance for subordinates, a healthy and professional working climate, and continuous development of leadership competencies.